"Fear the Flu, Not the Flu Shot": A Test of the Extended Parallel Process Model. Issue 11 (2nd November 2019) - Roberto, Anthony J.; Mongeau, Paul A.; Liu, Yanqin; Hashi, Emi C.
Abstract : This study investigates the effects of manipulated threat and efficacy on college students' attitudes, intentions, and behavior toward receiving the influenza vaccine (flu shot). Meta-analysis results indicate that during the nearly 70-year history of fear-appeal research, as few as six studies have orthogonally manipulated threat and efficacy, randomly assigned participants to conditions, and included a behavioral dependent variable. While there may be several practical reasons for this, it is problematic theoretically. The primary goal of this study is to add to this small but important body of literature. We tested the Extended Parallel Process Model, utilizing a 2 (high threat/low threat) × 2 (high efficacy/low efficacy) between-subjects design with random assignment to conditions. Dependent variables were attitudes and intentions regarding the flu shot (measured immediately after reading the message at Time 1) and flu shot behavior (measured 30 days later at Time 2). Results indicate that participants in the high threat condition reported greater perceived severity, susceptibility, and fear than participants in the low threat condition; and that that participants in the high-efficacy condition reported greater self-efficacy and response-efficacy than individuals in the low efficacy condition. Nonetheless, the predicted threat × efficacy interaction was not observed for attitude, intention, or behavior. Instead, there was a main effect for efficacy (but not threat) on attitudes and intentions, and no effect for either efficacy or threat on behavior. The theoretical and practical implications of these findings are discussed.